Coastal Feasts: A Pleistocene Antiquity for Resource Abundance in the Maritime Deserts of North West Australia?. (2nd January 2017) - Veth, Peter; Ward, Ingrid; Manne, Tiina
ABSTRACT: Located on the edge of Australia's North West continental shelf, Barrow Island is uniquely located to address a number of research questions, such as the antiquity and changing nature of Indigenous occupation, including shifting uses of regional economic resources in response to post-glacial sea-level rise. These questions are addressed from a range of archaeological, zooarchaeological, and geoarchaeological disciplines. Although only preliminary, results to date indicate the presence of marine resources dating to before sea-level stabilization (∼ 7.5 ka) that contain both dietary and utilitarian species, including high-ranked species such as sea turtle. The marine assemblages reflect a variety of habitats and substrates with a 17, 000-year record for the presence of a former tidal marsh or estuary. We also note recently obtained 14 C and OSL dates that extend the dietary marine faunas and initial occupation to well before 41 ka. This demonstrates that consumption of coastal resources began prior to the Holocene, when we begin to observe more widespread evidence of marine resource exploitation in the broader Canarvon Bioregion of northwest Australia. This evidence supports arguments for further research to directly test both the productivity of, and human reliance on, marine habitats from initial occupation.